IoT-Based Chili Plant Watering Automation Using Fuzzy Logic - Somantri, Nivika Tiffany; Riski Permana, Yoga; Charisma, Atik; Basuki, Sofyan; Ketut H, Ni; Setiawan, Antrisha D. (Universitas Negeri Padang, 2025)
Like humans, plants need water for growth and development. Where water plays an important role in the process of photosynthesis and transpiration as the main component in the photosynthesis process. Chili plants require several nutrients such as water and sunlight to produce the best quality chili. In an effort to improve the efficiency of watering chili plants, this research proposes an Internet of Things (IoT) based watering automation system using fuzzy logic. The system is designed to measure several environmental parameters such as soil moisture, air temperature, and relative humidity level, and use the data to make the right watering decision. This system will make it easier for chili farmers to take care of their plants without having to pay attention to the plants all the time. In this research, the system is designed using fuzzy logic using an ESP8266 microcontroller so that the system can be integrated with the web. The fuzzy logic system will produce an output in the form of a watering requirement level that is in accordance with the current environmental conditions based on data from existing sensors. These results will be used to control the watering actuator in the form of a water pump. All existing data will be integrated with the web to find out the condition of chili plants. After testing and analyzing the tool that has been made, the tool functions properly in accordance with the design. The tool will only water when conditions require watering. Then for all data taken will be integrated with the existing web. The analysis shows that testing the ambient air temperature with 10 different experiments has an average error of 1.41%, while testing the ambient humidity has an average error of 0.14%. And for testing the height of the water storage area has an average error of 5.43%.Keywords— ESP8266, Internet of Things (IoT), Fuzzy Logic, Chili Plants.